Evaluation of Anticancer Activity of Boswellic Acid and Montelukast Sodium against Human Prostate Cancer Cell Line PC-3: Anticancer activity of Boswellic Acid and Montelukast Sodium - Tejal Gandhi,; Khushboo Gandhi,; Kinnar Monapara, (Iranian Journal of Pharmaceutical Sciences, 2016)
Prostate cancer is a devastating disease for which current therapies are inadequate. Various lines of evidences have suggested the 5-lipoxygenase (5-LOX) pathway and the leukotriene receptor pathway are potential targets for prevention or treatment of Prostate cancer. Thus, search for new anti-cancer drugs targeting 5-LOX and leukotriene is very essential and important. The objective of the present study was to evaluate the in vitro anti- cancer effects of 5-LOX inhibitor-Boswellic acid and cysteinyl leukotrienes receptor antagonist-Montelukast sodium by 3-(4,5-dimethylthiazol-2-yl) -2,5-diphenyltetrazolium bromide (MTT) assay and Sulphorodamine B assay (SRB) against human prostate cancer cell line PC-3. Cell viability was assayed by trypan blue dye exclusion assay. A study was carried out in 24, 48, and 72 hours. In addition, effect of combination of both the above drugs was also determined by the same assays. Boswellic acid and Montelukast sodium demonstrated a substantial anti-cancer effect against the PC-3 cell line. The cytotoxicity of both the drugs increased with increase in duration of drug treatment. A combination of both drugs showed significant reduction in cell viability but did not show any synergistic activity. Complete dose-response curves were generated and IC50 values were calculated for all the assays. IC50 Value for Boswellic acid was found to be 49.15- 45.80 μg/ml and 50.14-43.39 μg/ml by MTT assay and SRB assay, respectively at the same time IC50 value for Montelukast sodium was 49.27-46.77 μg/ml and 46.68-46.47 μg/ml by MTT assay and SRB assay respectively. In summary, Boswellic acid and Montelukast sodium are likely to be valuable for the treatment of prostate cancer, but further studies are required for their more extensive biological evaluations.